Energy transition by conviction or by surprise?: environmental policy from 2009 to 2013 - Huß, Christian (German politics, 2014)
With the inauguration of the new federal government in 2009, many Germans were afraid of a rollback in energy and climate policy. Indeed, Christian democrats and liberals extended the operational lifespan of nuclear power plants but also continued with the previous green energy policy, known as Energiewende (energy transition). Beginning with a strong ideological separation, the Fukushima accident in Japan provoked a u-turn in nuclear policy, leading the government to abandon the lifespan extensions and to intensify the implementation of Energiewende, which became one of the core policy projects of the Merkel II cabinet then. Moreover, a new kind of consensus atmosphere was established which helped to settle some controversial environmental problems. Albeit policy outcomes concerning Energiewende were rather mixed, energy and climate policy was a rather low ranking issues during the federal election campaign in 2013.
Gesehen am 14.07.2020